(untitled) (Bangladesh Medical Journal, 2021)
The Suppression of gastric acid by long term use of PPI may decrease iron and vitamin B12 absorption and might be causing iron and vitamin B12 deficiency anaemia. This comparative cross-sectional study was conducted among patients with peptic ulcer disease from November 2017 to March 2020; attending in the Internal Medicine department of Bangabandhu Sheikh Mujib Medical University (BSMMU). A total of 80 patients were included and divided into group-A (PPIs user) and group-B (non-PPI user), each group containing 40 patients each. The group-A included patients who were taking PPIs for more than one year and aged from 18 to 70 years and group-B the control group who were not taking PPIs for atleast 1(one) year. The data were analysed by Statistical Package for the Social Sciences (SPSS) version 20.0 (SPSS Inc., Chicago, IL, USA).The study shown that male were 18(45%) and 19(47.5%) in group A and B respectively and female were 22(55%) and 21(52.5%) in group A and B respectively. The mean age of male and female was (year) 45.35 ± 12.46, 44.85 ± 15.24, respectively. Most of the patient took omeprazole 62.5% follwed by, esomeprazole 20%, pantoprazole 12.5%, rabeprazole 5%. About 47.5% of the patient took PPI for more than 2 years, and 52.5% took between 1-2 years. The mean (±SD) haemoglobin (Hb) level was 10.93±2.00 g/dl amongst group-A and 13.16±1.68g/dl in group-B, the difference is statistically significant (P<0.001). The mean serum iron of the PPI users (group-A) was 46.43±22.79, and of non-PPI users (group-B) was 84.95±33.18, the difference between iron level between two group was statistically significant (odds ratio -6.38 ; CI-2.28-17.84 and P-value <0.001). The PPI user group, mean vitamin B12 was 449±166.99 and in non-PPI group it was 432.85±175.93, which was statistically nonsignificant (P-value -1.00). Amongst all the participant low serum concentrations of iron, ferritin and transferrin were found 23(57.5%), 18(45%) and 27(67.5%), respectively in Group-A (PPI user group) and 7(17.5%), 7(17.5%) and 8(20%) respectively in Group-B (PPI-non user).The difference was statistically significant (p<0.05) between the two groups. But the value of TIBC was found to be high in 36 (90.0%) participants in both groups, which was statistically non-significant(p=0.33). Hematocrit (HCT) were low in 35 (87.5%) participants in Group-A and 25(62.5%) in Group-B. The difference was statistically significant (p<0.05). Low MCV was found in 10(25%) in the PPI user group and 4(10%) in the non-user group, whish was statistically non-significant. No significant differences in vitamin B12 concentrations (pg/ml) 449±166.99 vs 432.85±175.93 were found between groups A and group B, respectively. There was a weak negative Pearson’s correlation shown in ascatter diagram between duration of PPI use, and the iron level of group A (n=40) (r=-.311, p=.051). A negligible Pearson’s correlation was seen in the scatter diagram between the duration of PPI use, and vitamin B12 level of group A (r=+.05 p=.977). This study showed a significant decrease in haemoglobin, haematocrit, iron, ferritin, transferrin saturation in participants taking PPIs for more than one year, compared with age and gender-matched controls. No significant change of MCV, TIBC (Total Iron Binding Capacity) and vitamin B12 were noticed between groups. In conclusion, the study found a significant decrease in hematologic indices and iron profile among patients receiving PPIs for longer than one year. There was no substantial change of Vitamin B12 levels was detected between long-term PPIs users and non PPIs user groups. So, from the study it is suggested that judicial prescription of long-term PPIs must be practiced. However, the small sample size and short study duration were the limitation of the study. Bangladesh Med J. 2021 January; 50(1) : 27-32